O turismo indígena e sua contribuição para o empoderamento das comunidades indígenas da sub bacia do Rio Juruena-MT - Silvestre, Ronie Peterson (2024)
Indigenous peoples in several countries have sought ethnodevelopment through the introduction of tourism to maintain the integrity of their territories, ensure the perpetuation of their cultures, preserve natural heritage, and obtain additional income. However, negative effects of this activity, such as the commodification of culture, alienation of income, and environmental deterioration, can impact communities when they do not have autonomy over tourism activities. The objective of this research was to analyze how tourism developed by indigenous communities in the Juruena River basin contributes to their empowerment. The study covered nine villages of the HalitiParesi people located in the Utiariti and Ponte de Pedra Indigenous Lands, in the state of Mato Grosso. The research approach was qualitative and had exploratorydescriptive objectives. In-depth interviews, questionnaires, and unsystematic observation were used. Psychological empowerment was the dimension most highlighted by the participants, with emphasis on self-affirmation in transmitting the Haliti-Paresi culture to non-indigenous people, in addition to the self-esteem of individuals for feeling capable of assuming new roles in the community and feeling valued externally. Social empowerment was evidenced by training related to tourism, the general well-being of communities through the creation of infrastructure, in addition to the retention of young people in the villages. The participants are developing their visitation plans in accordance with FUNAI's IN No. 03/2015. As for political empowerment, tourism activities are led by the indigenous people themselves and the relationship with external agents has been one of cooperation, in addition to the creation of an exclusive tourism association. In its economic dimension, tourism has contributed as a supplementary income for most communities, with emphasis on the remuneration given to those involved in the activity, in addition to helping the communities with their most pressing needs. Regarding ecological empowerment, the Haliti-Paresi people have practically untouched territories. However, the waste produced by visitors is a factor that concerns them and is related to the resort modality, and indigenous leaders and external agents warn that communities should not have the resort as their main activity, and should dedicate more time to cultural tourism and community experience. Finally, it was found that territorial empowerment can reduce pressures and even possible invasions of indigenous territories through two possibilities: Presence, scope and movement and; Notoriety. This last dimension was proposed in this research, suggesting a new theoretical model: the Txini Model of empowerment and indigenous tourism.